A novel method for extracting geometric parameter information of buildings based on CSAR images. Issue 11 (3rd June 2022) - Li, Yishi; Chen, Leping; An, Daoxiang; Huang, Xiaotao; Feng, Dong
ABSTRACT: Compared with the traditional linear synthetic aperture radar (LSAR), circular SAR (CSAR) system can observe 360° of the observation area. In turn, more abundant scattering information in all directions of the observation area can be obtained, making it easier to observe the target information. Based on the observation advantages of CSAR, a new method for extracting geometric parameters of buildings is proposed in this paper. In this method, the scattering features of buildings on CSAR sub-aperture images and full-aperture images are extracted, and the corresponding relationship between the scattering features and building geometric parameters is deduced, and then the building geometric parameters are calculated. Through the above corresponding relationship, the geometric parameters of the building are calculated. At the same time, in this method, the advantages of CSAR omnidirectional imaging are used to extract the geometric parameters of buildings from multiple sub-aperture images. This method realizes the high-precision extraction of building geometric parameters by CSAR imaging for the first time. Finally, the experimental verification is carried out by introducing the measured data of the Ku-band autonomously measured, which confirms the effectiveness and accuracy of the proposed method.